Research and model studies on range action in Table Bay Harbour, Cape Town - Wilson, Basil Wrigley (Faculty of Science, 2020)
The demand for a model study of the Range problem in Table Bay Harbour was referred late in 1941 to the Research section of the Chief Civil Engineer's Department or the South African Railways and Harbours, the Research Engineer being requested to undertake an investigation. The Research Engineer at the time, Dr. C. V. von Abo. and the author commenced the task in January, 1942, by visiting Cape Town to sample nautical and technical opinion and study conditions, provisionally, on site.